Simulium ledangense, a new species of the Simulium feuerborni species-group of the subgenus Nevermannia (Diptera: Simuliidae) from Mount Ledang, Peninsular Malaysia - Ya’cob, Zubaidah; Takaoka, Hiroyuki; Sofian-Azirun, Mohd (Zootaxa, 2014)
Simulium (Nevermannia) ledangense sp. nov. is described from females, males, pupae and mature larvae from Peninsular Malaysia. This new species is assigned to the Simulium feuerborni species-group of the subgenus Nevermannia, and is characterized by the pupa having a very long stalk of the ventral paired gill filaments, which is almost five times longer than the interspiracular trunk and female tergites of segments 2 and 5 to 7 shiny. Taxonomic notes are given to distinguish this new species from three known species of the S. feuerborni species-group from Malaysia.